Self-Efficacy Beliefs of Yemeni Graduate Students about themselves as Competent Researchers - Al-Mekhlafi, Mohammad Abdu Ahmed; Al-Mekhlafi, Osamah Mohammed Abdu (Journal of Humanities & Social Sciences, 2023)
The current research study aimed at exploring the self-efficacy beliefs of Yemeni graduate students about themselves as competent researchers. The data of this study were collected via survey questionnaires that were created electronically using Google Forms and the link was sent to the graduate students in the Yemeni universities using the social media such as Facebook and WhatsApp. (113) questionnaires were returned. The sample consisted of 57 (50.44) Master’s program students and 56 (49.56) doctoral (Ph D) program students who are enrolled in the Yemeni universities. Similarly, the sample also consisted of 55 (48.7%) male graduate students and 58 (51.3%) female graduate students. The results indicated that the highest mean average among the six components of self efficacy beliefs was the subscale of Research Procedures (M= 4.26), followed by the domain of the nature of References (M= 4.25) and the subscale of the Topic Selection and Introduction (M= 4.18). Then, in the fourth and fifth places came the subscales of Results Presentation and Literature Review with the means of (4.17) and (4.07) respectively. The domain with the lowest mean was the domain of the Supervisor’s Role (M= 3.88). This research article reported statistically significant differences among the doctoral and MA students on the self efficacy beliefs in favor of the doctoral program students. On the other hand, gender differences were not found statistically significant. The study ends with some pedagogical implications and future research directions.